Assessment of the craniocaudal stability of four extracapsular stabilization techniques during two cyclic loading protocols: A cadaver study. Issue 7 (29th August 2013) - Choate, Christina J.; Lewis, Daniel D.; Conrad, Bryan P.; Horodyski, Mary Beth; Pozzi, Antonio
Abstract Objective To (1) compare the effect of cyclic loading on craniocaudal tibial translation in cranial cruciate ligament (CrCL)‐deficient stifles after extracapsular stabilization, and (2) evaluate the effect of peak force during cyclic loading on the rate of development of craniocaudal laxity. Study Design Biomechanical cadaveric study. Sample Population Cadaveric pelvic limbs (n = 24 pairs) from skeletally mature dogs. Methods Twenty‐four pairs of stifles were randomly assigned to 4 stabilization groups: nylon leader lateral circumfabellar‐tibial suture (NLS); FiberTape lateral circumfabellar‐tibial suture (FTLS); TightRope (TR); or bone anchor (BA). Contralateral limbs were cyclically loaded to produce cranial tibial translation at peak forces of either 80 or 160 N. Craniocaudal displacement of the tibia was measured with a mechanical testing machine during cyclic loading with the CrCL intact, after CrCL transection, and after extracapsular stabilization. The number of cycles each construct underwent before reaching 200% and 300% of the mean craniocaudal displacement present during cyclic loading of the CrCL‐intact stifles was calculated. Number of cycles among treatment groups was compared with a Kruskal–Wallis test. P < .05 was considered significant. Results Mean ± SD translation before and after CrCL transection were 3.9 ± 0.6 and 14.6 ± 1.7 mm, respectively. TR constructs resisted significantly more cycles than NLS constructs before reaching 7.8 mm (200%) and 11.7 mm (300%) of translation when loaded to 80 N. No other differences between constructs were significant at a peak load of 80 N. All constructs reached 7.8 and 11.7 mm of translation in fewer cycles when loaded to 160 N than at 80 N. Conclusions TR constructs were most resistant to elongation during cyclic loading. Doubling the peak force during cyclic loading significantly decreased the number of cycles constructs withstood, supporting recommendations for restricting postoperative activity after extracapsular stabilization of the CrCL‐deficient stifle.